Mirages and Mad Beliefs : Proust the Skeptic - Prendergast, Christopher (Book collections on Project MUSE., 2013)
Marcel Proust was long the object of a cult in which the main point of reading his great novel In Search of Lost Time was to find, with its narrator, a redemptive epiphany in a pastry and a cup of lime-blossom tea. We now live in less confident times, in ways that place great strain on the assumptions and beliefs that made those earlier readings possible. This has led to a new manner of reading Proust, against the grain. In Mirages and Mad Beliefs, Christopher Prendergast argues the case differently, with the grain, on the basis that Proust himself was prey to self-doubt and found numerous, if indirect, ways of letting us know.